Dacron conduit with a stented porcine xenograft valve in the anatomic correction of transposition of the great arteries and subpulmonary stenosis. Issue 6 (December 1975) - Gonzalez-Lavin, L; Sparrow, A W
Abstract : A stented porcine xenograft valve, sutured into a woven Dacron tubular graft, has been used in the anatomic correction of D-loop, D-transposition of the great arteries, and subpulmonary stenosis. The main advantage of this technique is its simplicity and practicality, as both Dacron tubular grafts and stented porcine xenograft valves are commercially available.